PENATAAN KANAL BANJIR TIMUR SEMARANG - Krisma Adijaya; Wisnu Prianto; Suripin Suripin; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Semarang has two major channels namely Kanal Banjir Timr (KBT) and the Kanal Banjir Barat (KBB). KBT is a canal that functioned as a flood control of the eastern city of Semarang. The existing condition of KBT is no longer able to accommodate the existing flood discharge. At the end of March 2015, KBT overflowed and inundated the residential areas around it. The decrease capacity of KBT are caused by the high of sedimentation, isn’t appropriate river space, and garbage. Therefore, proper handling efforts are needed to improve KBT. The aim of this study is to design a plan of KBT. The concept of river restoration considers not only hydraulic aspect, but also environment around the river (Maryono, 2007). The design of KBT is divided into three steps, first step is hydrology analysis, second step is hydraulics analysis and the third is the step of design. The aim of hydrological analysis is to determine the flood discharge with the HSS Gama I method. The aim of hydraulics analysis is to determine the dimension of the KBT that able to accommodate the flood discharge using HEC-RAS software. The third step is to create a landscape designs of KBT space area and estimate the cost needed. Based on this study, the proposed discharge Q 50-year is 518.29 m3/sec. To accommodate the discharge the demension of KBT is enlarged from 21.2 m to 23 m at the upstream, from 35.7 m to 40 m at the middle stream and from 55.4 m to 65 m at the downstream. In the border area and the banks of the canal changes into green space area, parks and sports facilities area. Total costs required to implement them is Rp . 118,848,568,000.00 (A Hundred Eighteen Billion Eight Hundred Forty Eight Million Five Hundred Sixty Eight Thousand Rupias).